2022
DOI: 10.1113/ep090613
|View full text |Cite
|
Sign up to set email alerts
|

Early chronotype with metabolic syndrome favours resting and exercise fat oxidation in relation to insulin‐stimulated non‐oxidative glucose disposal

Abstract: Early chronotypes (ECs) are often insulin-sensitive, in part, due to physical activity behaviour. It is unclear, however, if chronotypes differ in resting and/or exercise fuel oxidation in relation to insulin action. Using the Morningness-Eveningness Questionnaire (MEQ), adults with metabolic syndrome (ATP III criteria) were classified as EC (MEQ = 63.7 ± 0.9, n = 24 (19F), 54.2 ± 1.2 years) or late chronotype (LC; MEQ = 47.2 ± 1.4, n = 27 (23F), 55.3 ± 1.5 years). Carbohydrate (CHO) and fat oxidation (FOX, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Glucose regulation is established to rely on adequate capillary blood flow for nutrient exchange with myocytes. We previously reported that later chronotypes had lower GIRs than early chronotypes, which was paralleled with less carbohydrate oxidation as well as non‐oxidative glucose disposal 17,38 . Herein, while GIRs were not statistically significant, there was a medium effect size.…”
Section: Discussionmentioning
confidence: 74%
“…Glucose regulation is established to rely on adequate capillary blood flow for nutrient exchange with myocytes. We previously reported that later chronotypes had lower GIRs than early chronotypes, which was paralleled with less carbohydrate oxidation as well as non‐oxidative glucose disposal 17,38 . Herein, while GIRs were not statistically significant, there was a medium effect size.…”
Section: Discussionmentioning
confidence: 74%
“…It is possible that the differences in BMI and WC cause the diurnal pattern of MVPA rather than the diurnal pattern causes changes of BMI and WC. Additionally, the biological clock may vary between individuals, which could lead to interindividual variability in responsiveness to physical activity [37]. Information regarding the chronotypes (i.e., morningness vs. eveningness) of study participants would have enhanced the validity of the study and the interpretation of the diurnal pattern of MVPA.…”
Section: Discussionmentioning
confidence: 99%
“…19 Interestingly, evidence also exists to suggest that the strength of the association between poor sleep quality and insulin resistance is dependent on chronotype, such that individuals with an evening chronotype may be at greatest risk. 20 Importantly, the evening chronotype has been linked to greater risk of depression and anxiety, 25 greater dietary energy density, 26 as well as reduced physical activity and lower cardiorespiratory fitness, 27 33 together indicating that sleep has effects specific to peripheral tissues that may contribute to or exacerbate metabolic disorders. 32 Finally, while all of the aforementioned studies have used multiple days (e.g., ≥4 days) of sleep restriction, the deleterious effects of short sleep on insulin sensitivity have been shown to begin after just 1 night of sleep restriction (4-h TIB) in healthy subjects.…”
Section: Epidemiologic Evidence On Sleep Disruptionmentioning
confidence: 99%